Age-Dependence of Some Trace Element Concentrations and their Ratios in Human Prostatic Fluid - Zaichick, Vladimir; Zaichick, Sofia (Journal of Aging Research And Healthcare, 2019)
The effect of age on Br, Fe, Rb, Sr, and Zn concentrations as well as on Zn/Br, Zn/Fe, Zn/Rb, and Zn/Sr content ratios in human prostatic fluid was investigated by 109Cd radionuclide-induced energy dispersive X-ray fluorescent microanalysis. Specimens of expressed prostatic fluid were obtained from 51 men (mean age 51 years, range 18-82 years) with apparently normal prostates using standard rectal massage procedure. Mean values (M ± SΕΜ) for concentration of trace elements (mg·L-1) in human prostate fluid were: Br 3.62±0.58, Fe 9.04±1.21, Rb 1.10±0.08, Sr 1.19±0.14, and Zn 573±28. Mean values for ratios of trace elements in human prostate fluid were: Zn/Br 523±103, Zn/Fe 105±16, Zn/Rb 661±63, and Zn/Sr 719±95. An age-related increase in Zn content and decrease in Br and Fe concentration was found. Moreover, the strongly pronounced increase in Zn/Br and Zn/Fe ratios was also observed.
Keywords: variations with age in composition of human prostatic fluid; trace element concentration; trace element concentration ratios; energy dispersive X-ray fluorescent analysis